Increasing The Performance Of A 500 W Small Scale Wind Turbine Through Blade Optimization With Low Wind Speed Computational Simulation Studies - Rhakasywi, Damora (ROTASI, 2025)
The world is currently facing a dual energy crisis of increasing energy needs and the negative impact of the use of fossil energy. Indonesia has large wind energy potential, spread across various archipelagic regions. Based on a study by the Ministry of Energy and Natural Resources (ESDM), the potential for wind energy in Indonesia reaches 20,000 GW, with an mean wind speed of 3-7 m/s, proper design of wind turbine blades is an important aspect to ensure optimal performance and energy efficiency under various natural conditions. This research examines the performance and strength of inverse taper type wind turbine blades for horizontal shaft wind turbines, and pays attention to the characteristics of the wind that blows in Indonesia. This research used the method: TSR (tip speed ratio) design, tip to root chord ratio with tip, airfoil variation and determination of two blade segments combine to optimize linear rotation of the reverse tapered blade. Changes are made by going through a shape and performance selection process to determine the best blade using the BEM (blade element momentum) approach. The best designed blade is made from pine wood and its structure is modeled using the finite element method (FEM) to evaluate its safety level when used. The study results show that the best blade produces a peak Cp of 0.486 at a tip speed ratio (TSR) of 5, with a TSR range for Cp above 0.3 reaching 6.444, and can be used at air velocities of up to 15 m/s featuring a factor of safety (FoS) of 1.020.